Ageless benefits of transradial access for percutaneous coronary revascularization. Issue 6 (15th November 2015) - Kim, Sun Moon; Moliterno, David J.
Key Points: Radial artery access for PCI is an independent predictor of reduced mortality and lower major bleeding events. In this report, use of radial artery access increased roughly from less than 20% in 2006 to great than 60% in 2012, with the lowest increase among octogenarians. Steadily increasing operator experience and improving equipment should make radial artery access the preferred approach in the overwhelming majority of cases—irrespective of patient age.